Playing the role of a ‘boundary organisation': Getting smarter with networking - Drimie, Scott; Quinlan, Timothy (Springer, 2011)
This paper discusses the practices of organisations that cross the boundary between research and politics, to promote evidence-based policies and programmes.It uses the experience of a network of organisations in Africa to describe the methodology, challenges and successes of efforts to promote utilisation of research on the inter-connections between HIV/AIDS, food security and nutrition in South Africa. It emphasises that crossing the boundary between science and politics can be done systematically and is inevitable for any attempt that seeks influence policy making.The paper reveals the complexity of the research-policy making interface and identifies key lessons for the practice of networking and engaging policy and decision-makers.The concept of boundary organisation is a helpful means to understand the methodological underpinnings of efforts to get research into policy and practice and to understand the 'messy' process of doing so.